PENINGKATAN POTENSI WISATA HALAL DI PESANTREN BANDUNG KULON: PENDEKATAN CBPR - Sulianti, Ambar; Imam Sunardi; Supenawinata, Anwar (LPPM STAIMAS WONOGIRI, 2024)
Pesantren in Bandung face the challenge of balancing Islamic traditions with modern lifestyles. Developing the concept of halal tourism serves as a solution to address this issue. The service in Bandung Kulon District aims to enhance the potential of halal tourism in local pesantren through a Community-Based Participatory Research (CBPR) approach. The service is completed in 4 phases. Phase I: Laying the Foundations, resulted in an increased competency in understanding the importance of halal literacy and motivation to explore halal tourism. In Phase II: Research Planning, partner pesantren formulated research questions and mapped halal food in their vicinity. As a result, 3 potential pesantren were identified for coaching by the Small and Medium Enterprises Cooperative Office of Bandung City. In Phase III: Gathering and Analyzing Data, data were collected, analyzed, and interpreted using various tools, leading to the assessment that only Pesantren Darulsalam Al Mubarokah is sufficiently prepared to develop halal tourism with the Agrowisata Halal Jamur Tiram plan. In the final phase: Acting on Findings, the service team acted as facilitators to assist pesantren in implementing behavioral changes related to halal tourism, such as contacting Jabar Preneur to organize mushroom cultivation training based on the previous FGD results. The outcome of the service shows an improvement in the capacity of halal tourism at the partner pesantren. Keywords: halal tourism, pesantren, CBPR